Meta-Analysis of Randomized Controlled Trials Comparing the Long-Term Outcomes of Carotid Artery Stenting Versus Endarterectomy. (October 2015) - Vincent, Sophie; Eberg, Maria; Eisenberg, Mark J.; Filion, Kristian B.
Abstract : Background—: Stenting is an endovascular alternative to endarterectomy for the management of carotid stenosis, but its long-term safety and efficacy relative to endarterectomy remain unclear. Our objective was to compare the safety and efficacy of stenting with those of endarterectomy, with a particular focus on long-term outcomes, via meta-analysis of randomized controlled trials (RCTs). Methods and Results—: We systematically searched PubMed, EMBASE, MEDLINE, and the Cochrane Library for RCTs with ≥50 patients that compared stenting with endarterectomy in patients with carotid stenosis. Periprocedural and long-term outcomes were assessed, with data pooled across RCTs using random-effects models. Eight RCTs were included in our meta-analysis (n=7091), with follow-up ranging from 2.0 to 10.0 years. When compared with endarterectomy, stenting was associated with an increased risk of periprocedural stroke (relative risk, 1.49, 95% confidence interval [CI], 1.11 to 2.01; risk difference, 1.7%; 95% CI, 0.3 to 3.0) but a decreased risk of periprocedural myocardial infarction (relative risk, 0.47; 95% CI, 0.29 to 0.78; risk difference, −0.4%; 95% CI, −0.8% to 0.1%). During long-term follow-up, stenting was associated with an increased risk of stroke (relative risk, 1.36; 95% CI, 1.16 to 1.61) and a composite end point of ipsilateral stroke, periprocedural stroke, or periprocedural death (relative risk, 1.45; 95% CI, 1.20 to 1.75). Conclusions—: Although stenting has more favorable periprocedural outcomes with respect to myocardial infarction, the observed increased risk of stroke and death throughout follow-up with stenting suggests that endarterectomy remains the treatment of choice for carotid stenosis. Abstract : Supplemental Digital Content is available in the text.